Proximal Humerus Fractures in the Elderly: Concomitant Fractures and Management - Zachariasen, Kelly (Kans J Med, 2020)
INTRODUCTION: The purpose of this study was to identify additional injuries commonly seen with proximal humerus fractures experienced by patients 65 years or older and to evaluate discrepancies in the management of these patients with regard to provider type. METHODS: A retrospective review was conducted of all patients 65 years or older who sustained a proximal humerus fracture. Patient data collected included demographics, injury details, hospital course, and discharge destination. RESULTS: Patients with a concomitant fracture (45.5%, n = 65) had a slightly higher Injury Severity Score (ISS; 8.3 ± 3.0 vs. 6.4 ± 3.0, p < 0.001) and experienced one additional death than those with an isolated fracture (54.5%, n = 78). Slightly more patients were managed by a trauma provider (51.7%, n = 74) than by a non-trauma provider (48.3%, n = 69). Those managed by a trauma provider sustained the most pelvic fractures (12.2% vs. 2.9%, p = 0.038), were more likely to be injured in a motor vehicle collision (8.1% vs. 0%, p = 0.005), had a higher ISS (8.0 ± 3.3 vs. 6.4 ± 2.8, p = 0.003), and had more imaging performed than those treated by a non-trauma provider. There was, however, no difference in operative rates, concomitant injuries, length of stay, or discharge disposition regarding provider type. CONCLUSION: It is important to recognize proximal humerus fractures as a sign of fragility and to optimize hospital management of these patients.